Restrictions on academic freedom and university autonomy in Venezuelan Jurisprudence (2010-2019) - Gómez Gamboa, David Augusto; Villalobos Fontalvo, Ricardo Alberto; Romero La Roche, Diana (Frónesis, 2019)
The present paper summarizes the Case-Law tendencies regarding university autonomy in the Bolivarian Republic of Venezuela during 2010- september 2019 according to international standards on academic freedom and institutional autonomy. Some decisions issued by the Supreme Court of Justice (Constitutional and Electoral Chambers) and Courts with competence in administrative matters are analyzed, concluding that some of them contain restrictions against academic freedom and university autonomy in contravention with Venezuelan Constitutional Law (see Article 109 and 102 Venezuelan Constitution) and international instruments on human rights (Article 13 of the International Covenant on Economic, Social and Cultural Rights). The State violates international standards on the matter, as well as its domestic law, contravining its international commitments. In the context of international responsibility, the State should take the necessary actions to rectify its judicial precedents according to human rights standards, as indeclinable duty. Methodologically, this research is document-based.